Safety Assessment of Acer tegmentosum Maxim. Water Extract: General Toxicity Studies in Sprague–Dawley Rats and Beagle Dogs With Re-evaluation of Genotoxic Potentials - Park, Jin-Sung; Kwon, Euna; Kim, Yun-Soon; Kim, Sang-Moo; Kim, Dae-Sun; Jang, Ja-June; Yun, Jun-Won; Kang, Byeong-Cheol (Frontiers in Pharmacology, 2021)
Acer tegmentosum Maxim., commonly known as Manchurian stripe maple, is a deciduous tree belonging to the family of Aceraceae and has been traditionally used in folk medicine for its remedial effects in liver diseases and traumatic bleedings. With a growing body of experimental evidence for its pharmacological efficacies such as neuroprotective, hepatoprotective, antioxidant and anti-inflammatory activities, A. tegmentosum has gradually gained popularity as health supplement and functional food. However, the large part of essential toxicity information still remained lacking despite the possibility of mutagenic potentials as previously suggested, posing safety concerns in human consumption. In this study, we evaluated 90-day repeated oral toxicity of A. tegmentosum Maxim. water extract (ATWE) in SD rats with acute toxicity assessment in beagle dogs, and re-evaluated genotoxicity using a combination of in vitro and in vivo assays. During the oral study period, ATWE did not cause toxicity-related clinical signs and mortality in rodents without adverse effects observed in analysis of hematology, serum biochemistry and histopathology, establishing > 5000 mg/kg BW as NOAEL. In addition, doses up to 5000 mg/kg BW did not cause acute toxicity in beagle dogs. When assessed for genotoxicity using bacterial reverse mutation, chromosome aberration and micronucleus formation, ATWE showed lack of mutagenicity and clastogenicity. These results demonstrated that AWTE was safe in the present preclinical study for systemic toxicity and genotoxicity at the tested doses, providing a guideline for safe use in human.